Thinking Outside the Frame: Impacting Genomes Capacity by Programmed Ribosomal Frameshifting - Riegger, Ricarda J.; Caliskan, Neva (Frontiers in Molecular Biosciences, 2022)
Translation facilitates the transfer of the genetic information stored in the genome via messenger RNAs to a functional protein and is therefore one of the most fundamental cellular processes. Programmed ribosomal frameshifting is a ubiquitous alternative translation event that is extensively used by viruses to regulate gene expression from overlapping open reading frames in a controlled manner. Recent technical advances in the translation field enabled the identification of precise mechanisms as to how and when ribosomes change the reading frame on mRNAs containing cis-acting signals. Several studies began also to illustrate that trans-acting RNA modulators can adjust the timing and efficiency of frameshifting illuminating that frameshifting can be a dynamically regulated process in cells. Here, we intend to summarize these new findings and emphasize how it fits in our current understanding of PRF mechanisms as previously described.